STUDENT STRATEGIES IN PRACTICING PRONUNCIATION THROUGH ENGLISH MOVIE - Alan Jaelani; Audrya Dwiputri Anjani (English Didactic, 2021)
The purpose of this research is to report how high school students use movies as a strategy to practice English pronunciation. This research is a qualitative research with a case study design. The subject of this research involved 29 students from a SMK in Bogor. The instruments used in this study were questionnaires and interview. The results show that students’ strategies in learning anad practicing English pronunciation using moviesinvolve (1) The watching movies frequency (2) the use of Indonesian subtitles (3) the use of English subtitles (4)  note-taking for newly discovered vocabulary. In accordance with the results of this study, practicing pronunciation using movies really helps students in learning English pronunciation.